Inflammatory pseudotumor-like follicular dendritic cell tumor of the spleen - Kwon, Heejin (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Kwon H. Inflammatory pseudotumor-like follicular dendritic cell tumor of the spleen. Turk J Gastroenterol 2018; 29: 124-6.